Antifungal activity of essential oils against cigarette mold - Chen, Wenyi (My University, 2020)
With the improvement of people's living standards, natural antifungal agents have been paid more attention to by the manufacturers of consumer products. Mildew of cigarettes is a major problem during storage of cigarettes and raises a health concern. Natural essential oils have the characteristics of broad-spectrum antifungal activity. They can be used as an ideal new type, low-toxicity, and highly effective antifungal agent for cigarettes. In order to have a better use of natural antifungal agents, it is important to study the antifungal activity of essential oils against cigarette mold. However, such kind of studies has been seldom reported. In this article, the mold from cigarettes were isolated and identified by the methods of fungal morphological observation, microscopy, and 18SrDNA-ITS sequence determination. The antifungal activity of different active ingredients of essential oils against fungi before and after storage were studied by the method of measuring the inhibitory zone diameter (IZD) and minimum inhibitory concentration (MIC). As a result, fifteen strains of cigarette mildew fungi were identified from cigarettes. It was found that the molds were mainly Aspergillus, Penicillium, Cladosporium and Alternaria. Among them, Aspergillus brasiliensis was the most active one, with a colony diameter of 75.67 ± 0.89 mm. The results showed that the antifungal activity of four components of essential oils against A. brasiliensis was in the order: cinnamaldehyde> eugenol> citral> menthol. After accelerated storage, the antifungal activity of four essential oils all weakened.
Keywords: cigarette mold, essential oil, antifungal activity